Exploitation of bioactive molecules in the processing of microalgal biomass into biodiesel - Raposo, Ana Margarida Branco (2017)
Microalgae have been purported as a promising feedstock for the production of biodiesel, presenting a potential solution to overcome the high demand for transportation fuels. Although the production of biodiesel from microalgal biomass is feasible, the costs of production are not competitive when compared to those of fossil fuels. The biorefinery concept is a promising route to lower the costs of production of microalgal-based biofuels and enhance the final value of microalgal biomass. In this work, the potential of Tetraselmis sp. CTP4 for a biorefinery approach was evaluated, through a screening for bioactive compounds and biodiesel production. Crude (CB) and purified (PB) biodiesel were synthesized from wet microalgal biomass, and their properties were estimated based on the fatty acid methyl ester (FAME) profile obtained. Only the FAME, linoleic acid and PUFA (≥4 double bonds) contents, met the EN 14214 specifications in both. CB also met the iodine value defined in this regulation and the cetane number (CN) set in ASTM D6751 specification. Viscosity, density and cold filter plugging point (CFPP) were improved by the purification process. Concerning the biorefinery concept, three different types of activities were studied: Antioxidant, metal chelating and neuroprotection. Five different solvents were used on 2 different sources to produce the extracts: crude and spent biomass (after lipid extraction). The colloidal (CP) and water phases (WL) obtained in the crude lipid extract fractionation were also screened. The ethyl acetate, acetone and ethanol extracts from both crude and spent biomass, as well as the CP extract showed the highest antioxidant and metal chelating activities. As for the neuroprotection activity, the best results were obtained with the spent biomass extracts, using the same solvents mentioned above.